Association between internal carotid artery calcifications detected as incidental findings and clinical characteristics associated with atherosclerosis: A dental volumetric tomography study. Issue 145 (December 2021) - de Onofre, Niége Michelle Lazzari; Vizzotto, Mariana Boessio; Wanzeler, Ana Márcia Viana; Tiecher, Priscila Fernanda da Silveira; Arús, Nádia Assein; Arriola Guillén, Luis Ernesto; da Silveira, Heraldo Luís Dias
Highlights: Atherosclerosis early diagnosis is of great importance. Older patients usually undergo CT scans for implant placement. Dentists can be the first professional requested by patients before stroke. The dentist is able to identify calcifications in the internal carotid artery path. Abstract: Purpose: To evaluate the presence of calcifications in the internal carotid artery (ICA) in cone-beam computed tomography (CBCT), and to verify the association of these findings with sex, age, dental condition, and risk factors associated with vascular disorders. Methods: The CBCT scans used in this study were obtained from the database of a private dental clinic requested for the planning of rehabilitation with dental implants. The selection criteria were patients aged 40 years and above. Out of a pool of 1176 CBCT examinations, a total of 284 scans of adult patients were evaluated by two blinded observers. Data were collected from patients' medical records. Results: ICA calcifications were present in 63.0% of the examinations. Most calcifications were in the intracranial pathway (166). Despite being present in a smaller number 57 (C1), extracranial calcifications were more severe. Spearman's ρ coefficients (rS) indicated that the number of missing teeth was directly associated with the presence of calcifications (p = 0.042) and severity (p = 0.020). The age variable also had a direct relationship with the presence of calcifications (p ≤ 0.0001), increasing its frequency and severity over the years. In addition, hypertension (p = 0.036) and use of antihypertensive drugs (p = 0.015) were directly associated. Conclusions: There is a high occurrence of ICA calcifications in CBCT as incidental findings in adult patients, and it is directly associated with age, number of missing teeth and hypertension.